Faktor-Faktor Keputusan Pembelian dan Kepuasan Pelanggan (Literature Riview Manajemen Pemasaran) - Fikri Rizki Utama; Alika Nuri Syahiroh; Alya Nafiza; Anisa Martha Sujiva; Annisa Adhelia Pratiwi; Hasrun Afandi UmpuSinga (Indo Publishing, 2025)
This study is a literature review that aims to analyze the factors that influence purchasing decisions and customer satisfaction in the context of marketing management. The focus of the study covers four main variables, namely product quality, service quality, price, and customer value. Analysis of various literature sources shows that product quality has a significant effect on purchasing decisions, while service quality, price, and customer value have a strong effect on customer satisfaction levels. In addition, previous studies have also revealed that other variables such as promotion, location, and service processes contribute to satisfaction and purchasing decisions. The findings of this literature review confirm that customer decisions and satisfaction are formed through a combination of interrelated marketing factors. Therefore, companies need to pay attention to all these aspects to increase competitiveness, retain customers, and encourage repeat purchases.